Experiência de adoecimento de pessoas com insuficiência renal crônica - Lemos, Patrícia de Lima (2014)
This is a socioanthropological study of qualitative approach that examined the experience of adult men and women with chronic renal failure (CRF), and on renal replacement therapy. Such disease is clinically defined as the progressive and irreversible deterioration of the kidney function. It is a disease of alarming rise level, and requires continuous treatment with hemodialysis and peritoneal dialysis, or permanent treatment by renal transplantation. The approach of the illness experience focuses on the person, in the subjective process of experiencing the illness. Data were collected based on the items of the Explanatory Model of Illness and on recorded interviews guided by the oral report and a semi-structured script, with four women and five men on hemodialysis, and a man in peritoneal dialysis. The technique of representation by drawings made by participants was used to complement the interviews, in order to understand the concepts of pathophysiology and the physical impacts of the CRF. As well as observations during the interviews, recorded in a field diary, in addition, there was the characterization of the subjects. The group of data was treated as thematic analysis. Based on the structure of the Explanatory Model, the results and discussions were organized from the themes, namely: process of discovery, concept and genesis of the CRF; body notions of the CRF; material and immaterial impacts, daily confrontations and future expectations. Regarding the concept, the use of metaphors for expression was common, such as „the cross I have to bear‟. The onset of illness is reported with the emergence of subjective and objective uncommon signs. The late diagnosis of CRF was recurrent among the cases, added to the wrong treatments, which have worsened the suffering of these people, becoming a biographical disruption. In the genesis of the disease, it was common to find multiple causal explanations intertwining in a story such as heredity, other chronic morbidities, inadequate dietary and water intake, amid poor living conditions and physical work in the past. The impacts revealed emotional and physical aspects, such as constant pain and weakness, as well as the stigma by the presence of arteriovenous fistula. The dependence on dialysis creates an ambiguous situation, with feelings of anger caused by the dependence, and gratitude for the treatment that keeps and saves their lives. The drawings showed generalized pain, marks caused by fistula and catheter, as well as the absence and/or changes in organs. The impossibility of travelling and working formally were the most emphasized by men, and women perceive the greatest transformations in the domestic sphere. Everyday strategies to confront the illness include the informal social support from family members, from other sick people and the formal support from health services. Future expectations reflect the possibility of a successful kidney transplant, the faith and hope in God, in the possibility of healing, or just immediatist projects of living day to day. The experience of renal illness, although the CRF can affect any person, is shaped and influenced by social inequalities. In face of sick men and women, it was possible to find singular experiences, idiosyncrasies and variations of gender, but also the convergence of experiences. Finally, it is pertinent that the health care is socioculturally more sensitive, more confluent and equitable to the real needs of people.